Perspectives in Gamete and Embryo Cryopreservation - Rienzi, Laura Francesca; Iussig, Benedetta; Dovere, Lisa; Fabozzi, Gemma; Cimadomo, Danilo; Ubaldi, Filippo Maria (Seminars in Reproductive Medicine, 2018)
Cryopreserved gametes and embryos are a major feature of human-assisted reproduction and patient care services, accounting for an increasing number of births worldwide. Since the first success obtained using frozen human spermatozoa, cryopreservation technology has been successfully extended to include oocytes and embryos, in a variety of both medical and nonmedical indications. Over the years, the available procedures have become widely implemented and the increasing evidence of its efficacy has contributed to acceptance of the technology. Nevertheless, a gold standard protocol that would be universally shared by clinics has yet to be definitively established and, therefore, research into cryopreservation of gametes and embryos cannot be considered concluded. Moreover, much effort should be committed to the definition and resolution of safety issues, the establishment of automation, and investigations about the potentiality of immature germ cells or stem cells.
Keywords: gamete; embryo; freezing; vitrification; fertility preservation